2014
DOI: 10.1177/0021989414553747
|View full text |Cite
|
Sign up to set email alerts
|

Canada

Abstract: International Prize, the National Book Critics Circle Award for Fiction, and three Governor General's Awards for English-language fiction. Eleanor Catton's The Luminaries was the winner of the 2013 Governor General's Award for fiction, and was also shortlisted for the Man Booker Prize. This gripping murder mystery, which takes place in a remote gold-mining frontier town in nineteenthcentury New Zealand, describes how three unsolved crimes link the fates and fortunes of twelve men. The award committee praised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The kinetics of the redox reaction of S 2 O 8 2-and NO 2 -was studied by a number of workers. Elamin (8,9) , who found that the oxidation of nitrite ion by peroxodisulphate was second order, being first order with each reactant.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…The kinetics of the redox reaction of S 2 O 8 2-and NO 2 -was studied by a number of workers. Elamin (8,9) , who found that the oxidation of nitrite ion by peroxodisulphate was second order, being first order with each reactant.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%